1987
DOI: 10.1136/jcp.40.11.1314
|View full text |Cite
|
Sign up to set email alerts
|

Cell death in granulomata: the role of apoptosis.

Abstract: SUMMARY Unequivocal apoptoses were seen by light microscopy in examples of leprosy, sarcoidosis, tuberculosis, Crohn's disease and foreign body granulomata. A limited electron microscopic investigation showed typical apoptotic bodies in both sarcoid and leprosy granulomata. The number of apoptoses and mitoses in granulomata were counted and their densities calculated. The wide variation in the results between individual lesions may reflect differences in disease activity.Current understanding of cell turnover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 10 publications
7
47
0
1
Order By: Relevance
“…(3. 6, 7) and the granulotnata of both sarcoidosis and leprosy (51). Apoptosis is found under irradiation and cytostatic therapy as well as during tumor regression (4,6,7,9).…”
Section: Biological Significancementioning
confidence: 91%
“…(3. 6, 7) and the granulotnata of both sarcoidosis and leprosy (51). Apoptosis is found under irradiation and cytostatic therapy as well as during tumor regression (4,6,7,9).…”
Section: Biological Significancementioning
confidence: 91%
“…The integrity of granulomas is a critical determinant of the outcome of mycobacterial diseases, and apoptosis and necrosis are common events in granulomas associated with human tuberculosis (2,3,24,42,43). The mycobacteria-infected TNFRp55 Ϫ/Ϫ mouse may prove useful in defining suitable molecular targets for therapeutic interventions aimed at reducing tissue-destroying and lifethreatening immunopathology caused by an excess of T cells.…”
Section: Increased Numbers Of T Cells In Granulomatous Lesions Of Tnfmentioning
confidence: 99%
“…An early light microscopic survey of tuberculous granulomas reported the infrequent occurrence of cells with morphologic changes consistent with apoptosis. 45 Using the more sensitive in situ TUNEL method, Keane et al 22 examined lung sections from clinical cases of tuberculosis and estimated that 450% of cells in the periphery of granulomas were positive. Furthermore, Mancino et al (unpublished observations) found that in similar sections, typical tuberculous granulomata characterized by a core of caseous necrosis containing dying cells were surrounded by a cuff of apoptotic MF.…”
Section: Macrophage Apoptosis In Tuberculosis In Vivomentioning
confidence: 99%